Perbaikan Antarmuka dan Pengembangan Fitur Baru Situs Web Indonesian Future Leaders Chapter Malang menggunakan Framework Affordance-Based Design - Nissa Madaniyah Fadhilah; Retno Indah Rokhmawati; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
IFL Malang is an organization which moves on the field social education and accomodate the community in Malang to synergize together to positive change for Malang who has a website with bogger domain.The main purpose of the website is to facilitate readers to get to know more about IFL Malang. IFL Malang was intended to develop an new interface due to several reasons. The first reason is there are still shortcomings in user interface of the website, such as huge amount of information accumulation, less tidy layout, visualization of the image still minimalist and lack of a clear navigation on the website. The second reason is the limited blogger facility for the addition of Donation menu that will be developed in the future. Affordance-based design can offer designs with a theoretical foundation that sees the design components thoroughly and considers functions and users well together and shows not only shows the desired affordances but also unwanted affordances. The results of design improvements with the Affordance-based design method resulted in a new design that not only looked at the positive side but also the negative side of an affordance and strongly reflects the user. Affordances has a good influence on usability testing that is the aspect of effectiveness by generating a percentage of effectiveness 98.14% of the maximum value 100 %, There is no significant processing time so that it can be judged both on the aspect of efficiency and excellent value on all items of user satisfaction.